2020
DOI: 10.1083/jcb.202004164
|View full text |Cite
|
Sign up to set email alerts
|

Deorphanizing FAM19A proteins as pan-neurexin ligands with an unusual biosynthetic binding mechanism

Abstract: Neurexins are presynaptic adhesion molecules that organize synapses by binding to diverse trans-synaptic ligands, but how neurexins are regulated is incompletely understood. Here we identify FAM19A/TAFA proteins, “orphan" cytokines, as neurexin regulators that interact with all neurexins, except for neurexin-1γ, via an unusual mechanism. Specifically, we show that FAM19A1-A4 bind to the cysteine-loop domain of neurexins by forming intermolecular disulfide bonds during transport through the secretory pathway. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 58 publications
1
54
1
Order By: Relevance
“…Consistent with this conclusion, Nrxn1 ligands that appear to block the heparan sulfate modification of neurexins (i.e. CA10 58 and FAM19A1-4 59 ) are not expressed at appreciable levels in astrocytes (Extended Data Fig. 5g).…”
Section: Astrocytic Nrxn1 Forms Contacts With Both Neurons and Blood Vesselssupporting
confidence: 62%
“…Consistent with this conclusion, Nrxn1 ligands that appear to block the heparan sulfate modification of neurexins (i.e. CA10 58 and FAM19A1-4 59 ) are not expressed at appreciable levels in astrocytes (Extended Data Fig. 5g).…”
Section: Astrocytic Nrxn1 Forms Contacts With Both Neurons and Blood Vesselssupporting
confidence: 62%
“…FAM19A1 is a secreted protein expressed by specific subset of neurons located within several brain areas [24]. It has been demonstrated that FAM19A1 mediates posttranslational modification of neurexins, a family of presynaptic adhesion molecules involved in synaptic function [27]. In addition, ablation of FAM19A1 in mice led to several behavior abnormalities related to aberrant synaptic activities [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In Fam19a1 knock-out (KO) studies, behaviors of FAM19A1-ablated mice were characterized with hyperactive locomotor activity, longterm memory deficits, fear acquisition failure and feeding behavior abnormalities [24,25]. Moreover, recent studies have shown that FAM19A1 is an active participant in several neurophysiological functions and stimulates its binding partners, G protein-coupled receptor 1 (GPR1) and neurexins (NRXNs) [26,27]. It has been suggested that FAM19A1 could act as a pan-NRXN ligand providing functional diversification to NRXNs, presynaptic membrane-bound proteins that modulate synaptic activities [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Khalaj et al (2020) identified FAM19A, an “orphan” cytokine, as Nrx-binding protein from adult mouse brain. FAM19As bound with Nrxs through intermolecular disulfide bonds that were formed during intracellular transport.…”
Section: Functions Of Vertebrate Glypicans At Synapsesmentioning
confidence: 99%